NUCLEAR MAGNETIC-MOMENT OF RH-106 - Ohya, S; Ashworth, C; Nawaz, Z; Stone, N; Back, P (1990)
Nuclear orientation and nuclear magnetic resonance measurements have been performed for Rh106 oriented at low temperature in iron and nickel hosts. From the results of the temperature dependence measurements of nuclear orientation, the magnetic moment of Rh106 was deduced as (106Rh,1+)=2.52(5)N, which is very different from the value of 3.07(9) N reported previously. From the nuclear magnetic resonance on oriented nuclei measurements of Ni106, the magnetic hyperfine splitting frequency gNBHF/h was determined to be 441.5(7) MHz. Using the hyperfine field BHF (RhNi) of -22.49(5) T, the precise value of the magnetic moment of Rh106 was deduced: (106Rh,1+) =2.575(7) N. The electric quadrupole interaction has been measured using modulated adiabatic passage on oriented nuclei in a nickel single-crystal host. A broad distribution of the quadrupole splitting "Q is found, extending from 0 to 300 kHz. © 1990 The American Physical Society.